Penerapan Metode Prototype dalam Perancangan Media Pembelajaran Interaktif - Prio Kustanto; Ramadhan Bram Khalil; Achmad Noe'man (Program Studi Informatika Fakultas Ilmu Komputer Universitas Bhayangkara Jakarta Raya, 2024)
Interactive learning media is technology used in the learning process that allows users to interact actively with lesson material. Users can access it via devices connected to the internet via a web-based learning media platform. This learning platform provides the flexibility to access lessons freely, without being limited to location or time schedule. User needs analysis, prototype design, implementation, and platform testing are part of the research process. One approach that can be used in the system design process is the prototype method. The research objective is to create an interactive learning media platform for computer programming using the prototype method. Test results using the prototype method increase the functionality and responsiveness of the learning platform. To enhance the programming learning experience, the platform offers interactive video tutorial features and achievement or ranking features. This research is successful because it can create a platform that is not only informative but also interesting, which makes learning programming more fun and effective.